Examination of Pre-Service Science Teachers’ Argumentation Based Science Lessons: Case Study - Emrah Hiğde; Hilal Aktamış (Elementary Education Online, 2023)
The aim of this study was to determine pre-service science teachers’ views about argumentationbased science lessons and argumentation processes in practicum. 9 trainees from pre-service science teachers were chosen via the typical case sampling technique, as a purposeful sampling technique. At the beginning of the study, participants attended to pre-service education program about how teachers integrate argumentation in their science lessons. Semi-structured interviews realized with participants who successfully completed this education program and perform science lessons in the practice school. The findings of the interview data pointed that argumentation has some advantages in science education. Pre-service argumentation based science education course was sufficient and can be also improved. Pre-service science teachers enjoyed with attending argumentation activities in classroom and improving their argumentation based activities by revising. They gave a place to different argumentation activities in their lessons. By using the observation form, called “Coding of Argumentation Processes” by Simon, Erduran and Osborne (2006), it has been investigated how pre-service science teachers stimulated students to integrate into argumentation processes. The observation data revealed that pre-service science teachers perform more behaviors related to processes such as “Talking and Listening”, “Positioning”, “Constructing arguments”, “Justifying with Evidence” and “Evaluating arguments” in their lessons but they did not perform any behavior related to the processes such as “Counter arguing/debating” and “Reflecting on Argumentation Process”.